A novel near-infrared fluorescent probe for rapid sensing of HClO in living cells and zebrafish - Li, Liangliang; Wang, Xiaofeng; Huang, Jinzhi; Ma, Kaidong; Tan, Xiaoyu (Frontiers in Chemistry, 2022)
Reactive oxygen species (ROS) are significant active species in living organisms, and their coordination maintains the function of organelles to resist the invasion of foreign substances. Hypochlorous acid (HClO) is not only an eventful signaling species but also a kind of ROS, which plays an irreplaceable role in the immune system. However, its abnormal levels can cause cell damage or even apoptosis, which in turn leads to the onset of a series of diseases such as inflammation, neurological diseases, and even cancer. Based on this, we designed a near-infrared fluorescent probe with a large Stokes shift for ultrafast response to HClO. Furthermore, the probe exhibits excellent sensitivity and selectivity toward HClO over other species. The probe was successfully applied to visualize endogenous and exogenous HClO in living cells and in zebrafish. This unique study is the key to providing a trustworthy tool for imaging based on the in vitro and in vivo imaging of endogenous HClO, which possesses great potential for the use in future studies of HClO-related biology and pathology.